2023
DOI: 10.1088/1361-6463/acbc2f
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic control of Fano-like interference in the graphene periodic structure

Abstract: We propose and investigate a graphene periodic subsurface structure consisting of a coplanar pair of ring resonators and a ribbon. The Fano-like interference can be actively regulated by the applied magnetic field, incident angle and Fermi energy. Since the excited charges of graphene monolayer have cyclotron properties in the external magnetic field, the transmittance and line-shape can be effectively controlled. At a certain frequency, different magnetic fields have different effects on the conductivity tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…10. The ON/OFF ratio and modulation depth, which are respectively expressed as Z = 10log 10 (A on /A off ) and MD = (A on /A off )/A on , are used to measure the performance of the Paper PCCP optical switch 41,42 where A on and A off represent the absorption of the ''ON'' and ''OFF'' states, respectively. When the proposed structure acts as a triple-frequency optical switch, Z and MD of Modes I, II and III are 19.03 dB, 11.47 dB and 22.03 dB, and 98.8%, 92.9% and 99.4%, respectively.…”
Section: Results and Analysismentioning
confidence: 99%
“…10. The ON/OFF ratio and modulation depth, which are respectively expressed as Z = 10log 10 (A on /A off ) and MD = (A on /A off )/A on , are used to measure the performance of the Paper PCCP optical switch 41,42 where A on and A off represent the absorption of the ''ON'' and ''OFF'' states, respectively. When the proposed structure acts as a triple-frequency optical switch, Z and MD of Modes I, II and III are 19.03 dB, 11.47 dB and 22.03 dB, and 98.8%, 92.9% and 99.4%, respectively.…”
Section: Results and Analysismentioning
confidence: 99%
“…The results provide an opportunity for plasma optical switch operation within the wavelength range of interest. ON/OFF ratio (η) and MD are important indexes of plasma optical switch, and its expression are as follows [26,40,41]:…”
Section: Results and Analysismentioning
confidence: 99%
“…The thickness of SiO 2 is set at 180 nm and the relative dielectric constant is 1.96 [26]. The thickness of E7 NLC is consistent with that of SiO 2 layer.…”
Section: Structure and Theorymentioning
confidence: 98%
“…For the system where no literature was found. [37,45] MoSi 2 P 4 9.4 3.45 138/4 0.62 1.07 0.86 0.21 1.17, 1.58 [45,46] MoSi 2 As 4 9.9 3.60 181/16 0.52 0.88 0.69 0.19 1.01, 1.60 [45,46] MoSi 2 Sb 4 10.9 [43,44] WSi 2 P 4 9.4 3.45 439/6 0.30 0.65 0.45 0.20 0.93 [44] WSi 2 As 4 9.9 3.60 503/25 0.21 0.47 0.29 0.18 0.67 [44] WSi 2 Sb 4 10.9 The most striking feature in the electronic structures of MSi 2 Z 4 is the absence of the Λ valley between the high-symmetry points Γ and K near the CBM, in contrast to conventional TMDCs, [24,25,61,62] see Figure 2 and, for schematic visualization, Figure S6, Supporting Information. It is worth noting that a feature analog to the Λ valley is still present in the band structure of the MSi 2 N 4 but it is energetically much higher than the CBM at K compared to the Λ-valley in the TMDCs.…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…[34,37,41] Similar to the TMDCs, different MSi 2 Z 4 structures have been proposed and investigated, [42] with the so-called α phase being the most frequently studied. [37,[43][44][45][46] It was shown that this material and its siblings exhibit a tunable electronic structure including metal and halfmetal systems as well as semiconductors with direct and indirect bandgaps. [39] Furthermore, the ab initio evaluation of the photocurrent in ML MoSi 2 Z 4 (Z = P, As) under different energy and polarization of the incident light revealed that the absorption edge is insignificantly affected by the number of layers, suggesting their suitability for optoelectronic applications.…”
mentioning
confidence: 99%